If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 7x + -3 = 3x + -1x + 6 Reorder the terms: -3 + -2x + 7x = 3x + -1x + 6 Combine like terms: -2x + 7x = 5x -3 + 5x = 3x + -1x + 6 Reorder the terms: -3 + 5x = 6 + 3x + -1x Combine like terms: 3x + -1x = 2x -3 + 5x = 6 + 2x Solving -3 + 5x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 5x + -2x = 6 + 2x + -2x Combine like terms: 5x + -2x = 3x -3 + 3x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 3x = 6 + 0 -3 + 3x = 6 Add '3' to each side of the equation. -3 + 3 + 3x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 6 + 3 3x = 6 + 3 Combine like terms: 6 + 3 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 9(u+4)=2u-4 | | 16x^2+6x+66=0 | | (3x-9)(3x-9)-12=0 | | 5g+2g+2=12 | | x=1x(4x^2*2x) | | -6x-2-3x-1-3x-1=0 | | 3x^2-12x=-14 | | 3x+24=0 | | g-g+8g-3=114 | | x^3-2x^2-11x+10=0 | | x=2+2 | | 11x^2-5x-5=0 | | 20x+6-4x=12.0+6x | | 2x+2+3x-4= | | 2x+2+3x-4=1 | | 6x-7-2(x-5)=-5 | | 6x^2+4x+6=0 | | 3(5-x)-3+6x=42 | | 4g-2=34 | | -5x+3=4x-24 | | x+2=87 | | 2+5x=17-2x | | 6x^2-3=7x | | 8=0.75x | | 15y^2+28y+12=0 | | 18s^2(s+4)=0 | | 5x-2y+z=5 | | 1.3x+1.2y=3.9 | | y^4-20y^2+64=0 | | 4x-(3-x)= | | x-9y=-12 | | x*x=2y |